W-Repel / Mohd Aliffudin Jeffry - Jeffry, Mohd Aliffudin (Universiti Teknologi MARA, Kedah, 2018)
W-Repel is a first generation of specific repellent product that combined with clock system. The name of W-Repel is come from combination word "watch" and word"repellent". This repellent product is designed for repel from the insect that more specific for osquito in the shelter "house". W-Repel is use a parasitism concept which means related to the task on this semester about " symbiotic Concept". The ingredients to repel the mosquito is totally used a herbs which is " Serai Wangi".